Prevalence and associated risk factors of asymptomatic bacteriuria among antenatal women attending a health care center: one year study - Cooly, Vijayalakshmi; Bandaru, Sailaja; Salicheemala, Bhuvaneswari; Surayapalem, Sailaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Asymptomatic bacteriuria is defined as presence of persistent and actively multiplying bacteria in urine in significant numbers, ≥105/ml but without clinical symptoms. Detection of ASB is important during pregnancy as it leads to 25% of symptomatic urinary tract infection in pregnant mothers, pyelonephritis, hypertension in pregnancy, postpartum UTI, anemia, preterm labour, low birth weight and perinatal death of the foetus. The objective of the present study is to identify the prevalence of ASB among pregnant women, epidemiological pattern, risk factors associated with it, type of pathogens and their antimicrobial susceptibility. Methods: A prospective cross-sectional study was conducted on 500 asymptomatic antenatal women who fulfilled the inclusion criteria attending the department of Obstetrics and Gynecology. Mid stream urine specimen was collected from all the cases and subjected to microscopic analysis and culture and sensitivity. Results: Our study showed the prevalence of ASB as 7.6% among antenatal women.78.8% of sterile cases and 13.6% as contaminants. 21-25 years was the common age group of ASB cases in our study. ASB was common among multiparous women, during 3rd trimester. Statistically significant association was observed with low socio-economic status, increases sexual activity and among illiterate cases. Escherichia coli (42.11%) was the most common isolate in the study. Other isolates were Klebsiella, Staphylococcus aureus, CONS, Citrobacter and Enterococcus sp. Imipenem, Meropenem exhibited 100% sensitivity for gram negative isolates and clindamycin for gram positive isolates. Conclusions: All the cases of ASB diagnosed should be treated based upon the culture and sensitivity report to prevent unnecessary prescription of antibiotics which can economically burden the patient as well pave a way in development of resistant strains. Hence, further initiatives should be undertaken to include urine culture sensitivity as a part of national screening programme to prevent maternal and foetal complications.